SADAQAH AND ITS RELEVANCE TO PEOPLE’S ECONOMIC DEVELOPMENT: A SEMIOTIC ANALYSIS OF FERDINAND DE SAUSSURE - Saputri, Apik Anitasari Intan; Waliko, Waliko; Syah, Toufan Aldian; Basit, Abdul (DAS Institute, 2022)
This qualitative interpretative research aims at scientifically testing the signs and symbols of sharia economic values in the equitable distribution of justice in the Quran based on the semiotic discourse of the Quran and describes their significance in the economic sphere. Economic values and principles are presented in the Quran in Surah Al-Baqarah verse 261, which explains the meaning of charity with its seven-hundred-fold reward for whoever gives charity. Semiotics, as one approach to the Quran study, attempts to construct the meaning of language with a sign system. The marking interpretation method is to synergize between the mark and the marker, which leads to a new representation of the meaning. Based on semiotic reading, socio-economic justice may be realized through several ways: Eliminating monopolies; Guaranteeing all parties’ rights and opportunities for active participation in the economic processes, including production, distribution, circulation and consumption; Ensuring fulfillment of the basic needs of every community member; and conducting socio-economic security assurance mandate for survival and assisting the weak.